Aplicación de técnicas modernistas en la presentación visual de 4 platos típicos de Ibarra - Frías Chinguá, Bryan Jhoel (2022)
The present proposal focuses on the application of modernist techniques that allow a better visual presentation of four typical dishes of the city of Ibarra, in order to create an attractive plating in the sight of diners while preserving the flavor, color, aroma, texture and originality of typical dishes, since avant-garde cuisine involves the application of modernist techniques, molecular cuisine, and typical cuisine, will contribute to local competitiveness. The present investigation is applied and experimental with a mixed approach and aligned to the inductive-deductive, analytical-synthetic methods and the application of documentary, explanatory and experimental research, the techniques that were applied are: survey, interview and non-participant observation that were of great importance for gathering the required information. The type of sample used in this project was a non-probabilistic sample of coexistence, obtaining data in a simple, effective and local way. The survey was applied to people of legal age and with knowledge above the fourth level of gastronomy and the interviews were conducted with four experts with vast knowledge in gastronomy. Information was acquired about the typical cuisine, which has a defined scheme and its flavor is delicious, however, its presentation is no longer so attractive for many people, so the application of modern avant-garde techniques, in addition to giving it an attractive touch, also enhances the benefits in nutritional values of the typical kitchen. By observing and tasting a typical dish presented in a different way in relation to the traditional one, students and traditional chefs will be encouraged to experiment and innovate other typical dishes applying cutting-edge techniques with an adequate and organized methodological process, and to diversify Ibarra gastronomy, from in such a way that national and foreign tourists are attracted by the typical cuisine fused with the avant-garde cuisine.